2014
DOI: 10.4012/dmj.2013-158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acidic sodium fluoride-treated, commercially pure titanium on periodontal pathogens and rat bone marrow cells

Abstract: The purpose of the present study was to clarify the potentiality of acidic fluoride solution in treating peri-implantitis. We examined bactericidal activity of fluoride solution against periodontal pathogens; and evaluated the effects of fluoride on titanium, and the effects on cell proliferation and differentiation of rat bone marrow cells on the fluoride-treated titanium. Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis were used to determine minimal inhibitory concentration (MIC) and short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…F showed no or a slight inhibitory effect on the tryptone metabolism by Pg, Pi and Fn, as reported previously for Pg (Shimogishi et al, 2014). F is known to inhibit enolase, a glycolytic enzyme, as well as the sugar: phosphoenolpyruvate phosphotransferase system, an enzymatic system for sugar uptake in Sm (Kanapka and Hamilton, 1971).…”
Section: The Effects Of Antimicrobial Substances On Bacterial Metabolsupporting
confidence: 70%
See 1 more Smart Citation
“…F showed no or a slight inhibitory effect on the tryptone metabolism by Pg, Pi and Fn, as reported previously for Pg (Shimogishi et al, 2014). F is known to inhibit enolase, a glycolytic enzyme, as well as the sugar: phosphoenolpyruvate phosphotransferase system, an enzymatic system for sugar uptake in Sm (Kanapka and Hamilton, 1971).…”
Section: The Effects Of Antimicrobial Substances On Bacterial Metabolsupporting
confidence: 70%
“…The minimum inhibitory concentrations (MICs) on growth of these substances have been reported previously (Amorim et al, 2004;McBain et al, 2004;Shimogishi et al, 2014;Sreenivasan et al, 2013); however, their effects on the metabolic activity of periodontopathic bacteria are still unknown. Therefore, we also attempted to apply our new method to evaluating the effects of these antimicrobial substances found in oral care products on bacterial metabolic activity.…”
Section: Introductionmentioning
confidence: 99%
“…A. actinomycetemcomitans is mainly detected in aggressive periodontitis, a severe and rapidly progressing form which most often starts at an early age [90]. In this study, the growth of both bacteria was significantly [91]. A 6-month clinical study found that the fluoride containing dentifrice showed significant reductions in the number of anaerobic bacteria on both the dental implants and control teeth at 3 months [92].…”
Section: Discussionmentioning
confidence: 49%